Pd and In addition onto Au nanoparticles supported on TiO2 as a catalytic formulation for NO3 − reduction in water - Devard, Alejandra Veronica (2016)
The catalytic performance of Pd–In–Au/TiO2 was studied for the reduction of nitrites and nitrates in water and compared with that of Au, Pd, Pd–In, In–Au and Pd–Au supported on TiO2. Different characterization techniques were used to study the bulk and surface physicochemical properties of the trimetallic catalyst. The catalyst so obtained was active and stable in the nitrate reduction reaction, having a good selectivity to nitrogen. This improvement caused by the presence of gold is attributable to a strong interaction with surface palladium and can therefore act to regulate the hydrogenation activity of the Pd particles. Over 80% of Pd is deposited on top of the Au nanoparticles, which interact with surface Au during the reduction process. The NO2 − species is an intermediate product in the NO3 − reduction and the surface In–Pd intermetallic species are responsible for this first reaction step.